Pengaruh Kualitas Produk Dan Citra Merek Terhadap Minat Beli Konsumen Pada Dunkin Donuts Di Kota Bogor - Soedargo, Bayu Prasetyo; Nabillah, Aulia (Program Vokasi dan LPPM IBI Kesatuan, 2025)
ABSTRACT This study aims to 1) To find out whether Product Quality has an effect on Purchase Intention at Dunkin Donuts, 2) To Know Whether Brand Image has an effect on Purchase Intention at Dunkin Donuts, and 3) To find out whether Product Quality and Brand Image have an effect simultaneously on Interest Buy at Dunkin Donuts, especially for people in Bogor City. The number of samples used was 150 respondents using the formula hair et al. The data used is primary data derived from respondents' answers. Obtaining questionnaire data is 150 respondents with data processing using the Statistical Package For the Social Sciences (SPSS) with the Multiple Linear Regression Analysis method. From the results of this study, the following data were obtained: (1) Product Quality has a positive and significant influence on Consumer Purchase Interest at Dunkin Donuts, (2) Brand Image does not have a positive and significant influence on Consumer Purchase Interest at Dunkin Donuts, and (3) Product Quality and Brand Image simultaneously have a positive and significant effect on Consumer Purchase Interest at Dunkin Donuts. Keywords : Product Quality, Brand Image, Purchase Intention